Support Staff Performance and Client Satisfaction-Based Office Productivity in Higher Education: A Descriptive-Correlational Study - G A Batalla; R A Fernando; M Arcillas; J Cerdeña; J G Castillo; A L Barcenal; G Batalla; A Tolentino; F Malitig; L O Barrion (Applied Quantitative Analysis, 2026)
Support staff play an essential role in ensuring the efficient operation of higher education institutions, yet their contribution to office productivity remains underexplored. This study examined the relationship between support staff performance and the productivity of key offices at the City College of Calamba (CCC). Specifically, it assessed support staff performance in terms of work content, work behavior, job specification, work discipline, and job knowledge and competency, and evaluated office productivity through client satisfaction indicators such as responsiveness, reliability, access and facilities, assurance, and outcome.The study employed a quantitativedescriptive-correlational research design. Data were gathered using structured questionnaires administered to heads of offices and clients from 14 key offices, covering 40 support staff personnel. Descriptive statistics were employed to present the levels of staff performance and office productivity, while Pearson’s correlation coefficient was used to determine the relationship between support staff performance and the productivity of key offices. Findings revealed that support staff performance and office productivity were both rated very high. Moreover, a strong positive relationship wasfound between support staff performance and office productivity (r = 0.6333), indicating that higher support staff performance is associated with increased client satisfaction and improved office productivity. The findings highlight the important contribution of support staff to institutional effectiveness and service delivery in higher education institutions. The study provides practical implications for higher education administrators and policy-makers in strengthening staff development programs and improving organizational productivity.